NSM technique to increase the load carrying capacity of continuous RC slabs - Dalfré, Gláucia (2013)
This work presents and analysis the results of an ongoing research project on the use of the near surface mounted (NSM) carbon fiber-reinforced polymer (CFRP) laminates for the increase of the load carrying capacity of statically indeterminate (two spans) reinforced concrete (RC) slabs. The test program consisted of seventeen slab strips, grouped in two series that are different on the adopted strengthening scheme: H series, where H is the notation to identify the slabs strengthened with NSM CFRP laminates exclusively applied in the hogging region; HS series, where HS is the notation to identify the slabs strengthened with NSM CFRP laminates applied in both hogging and sagging regions. The program includes six unstrengthened reference RC slab strips, and eleven strengthened with CFRP NSM configurations designed to increase in 25% or 50% the load carrying capacity of the corresponding reference RC slabs. An extensive monitoring system was applied in the constituent materials, in the critical regions of the tested slabs, in order to collect information for the discussion about the effectiveness of NSM technique in terms of load carrying and moment redistribution capacity. The strengthening procedures adopted in the laboratory tests followed, as much as possible, the real strengthening practice for this type of interventions. The obtained results show that the proposed technique is able to increase significantly the load carrying capacity of statically indeterminate RC slabs, even for those with relatively high steel reinforcement ratios. The load carrying capacity of the strengthened slabs was limited by its shear capacity or by the detachment of the strengthened concrete cover layer. At failure of the strengthened slabs, the longitudinal steel bars at intermediate support (hogging region) and at loaded sections (sagging regions) have already yielded, and the deflection was quite large. However, for some strengthening configurations, the CFRP laminates led to a decrease of the moment redistribution capacity of the slabs.